2014
DOI: 10.4103/0975-7406.137255
|View full text |Cite
|
Sign up to set email alerts
|

Burning mouth syndrome: A review on its diagnostic and therapeutic approach

Abstract: Burning mouth syndrome (BMS), a chronic and intractable orofacial pain syndrome is characterized by the presence of burning sensation of the oral mucosa in the absence of specific oral lesion. This condition affects chiefly of middle aged and elderly woman with hormonal changes or psychological disorders. In addition to burning sensation, patient with BMS also complains of oral mucosal pain, altered taste sensation, and dry mouth. This condition is probably of multifactorial origin, often idiopathic and its ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 32 publications
4
74
0
5
Order By: Relevance
“…Ample research shows that prevalence of BMS varies considerably, between 0.7% and 15%, depending on the population investigated 5,[7][8][9][11][12][13][14] . For example, one study found age-adjusted prevalence rates of 18.8 and 3.7 cases in women and men, respectively in 100,000 people 15 , while another investigation discovered that BMS occurs in 1 in every 1,000 subjects, mainly in women over 50 years old 16 .…”
Section: Bms Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Ample research shows that prevalence of BMS varies considerably, between 0.7% and 15%, depending on the population investigated 5,[7][8][9][11][12][13][14] . For example, one study found age-adjusted prevalence rates of 18.8 and 3.7 cases in women and men, respectively in 100,000 people 15 , while another investigation discovered that BMS occurs in 1 in every 1,000 subjects, mainly in women over 50 years old 16 .…”
Section: Bms Epidemiologymentioning
confidence: 99%
“…Women are the most affected group, usually at a 7 to 1 ratio against men, 90% of whom are in the perimenopausal stage. Typically, BMS manifests three years before and as late as 12 years after the onset of menopause 2,4,[7][8][9]11,13,[18][19][20][21][22] .…”
Section: Bms Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Patient may also describe the symptom as tingling, scalding, annoying, tender or numb filling of the oral mucosa. The pain is primarily bilateral and typically on the anterior 2/3 of the tongue (71-78%) followed by dorsal and lateral border of the tongue, anterior portion of hard palate, labial mucosa or gingiva with no identifiable precipitating factors except stress and other psychological factors [14][15][16]42 . To fulfill the diagnostic criteria for BMS, pain episode must occur continuously at least 4-6 months 1,43 .…”
Section: Clinical Featuresmentioning
confidence: 99%